Ants (Hymenoptera: Formicidae) as Potential Mechanical Vectors of Pathogenic Bacteria in a Public Hospital in the Eastern Amazon, Brazil. Issue 5 (5th May 2020) - do Nascimento, Leonardo Espíndola; Amaral, Raquel Rodrigues; Ferreira, Ricardo Marcelo dos Anjos; Trindade, Diogo Vitor Soares; do Nascimento, Rafael Espíndola; da Costa, Tiago Silva; Souto, Raimundo Nonato Picanço
Abstract: Studies related to ants found in hospital environments have aroused interest in their role as mechanical vectors of pathogenic microorganisms. The objective of the current research was to determine the species composition and bacterial contamination of ant species found in a public hospital in the eastern Amazonian region. Ants were captured using bait containing honey and sterilized sardines in 15 locations within the Macapá Emergency Hospital, Amapá. Ants were identified morphologically using specific keys. Bacteria were first inoculed in a Brain Heart Infusion broth and then plated on 5% Agar with blood or MacConkey media. Bacterial species were identified through biochemical procedures. In total, 9, 687 ants were collected, with 69.8% from the dry season and 30.2% from the rainy season. Nine species of ants were identified belonging to three subfamilies: the Monomorium pharaonis (Linnaeus 1758) being the most common, comprising 39.2% of the total specimens. Only one ant species was found in each bait, facilitating microbiological analyses. In total, 92 bacteria isolates were identified comprising 12 species. Pseudomonas aeruginosa Schroeter 1872 (Pseudomonadales: Pseudomonadaceae) was pathogenic bacteria, most frequently isolated, comprising 10.9% of the positive samples. The most contaminated ant in the study was M. pharaonis with 38.3%. It was the dominant ant species in this hospital environment. Its wide prevalence, forage day and night of this vector in hospital facilitated bacterial contamination. The presence of bacteria on ants may be associated with the dissemination of pathogens which cause hospital infections, making pest control a necessity in these institutions.